2011
DOI: 10.3109/1061186x.2011.561856
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of pro-inflammatory cytokine suppression and survival by microencapsulated dexamethasone in the treatment of experimental sepsis

Abstract: Cytokine inhibiting drugs are much more effective when delivered intracellularly to phagocytic cells in the microencapsulated form. Dexamethasone is a powerful inhibitor of TNF-α cytokine through inhibition of NF-κB which is a gene regulator of multiple pro-inflammatory cytokines. We have determined the effect of microencapsulated dexamethasone in pro-inflammatory cytokine release both in in vitro using whole blood model, and in vivo using peritonitis model of septic shock. Microspheres of 1-4 μm mean size wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In this context, dexamethasone emerges as an attractive candidate because of its pleiotropic protective properties. In various cell types and animal models it inhibits the induction of MMPs, prostaglandins, inflammatory cytokines, nitric oxide, and other oxygen‐derived radicals . The literature is inconsistent on whether dexamethasone inhibits or promotes apoptosis in different types of cells but, as described below, it protects the viability of chondrocytes exposed to IL‐1.…”
Section: Dexamethasonementioning
confidence: 99%
“…In this context, dexamethasone emerges as an attractive candidate because of its pleiotropic protective properties. In various cell types and animal models it inhibits the induction of MMPs, prostaglandins, inflammatory cytokines, nitric oxide, and other oxygen‐derived radicals . The literature is inconsistent on whether dexamethasone inhibits or promotes apoptosis in different types of cells but, as described below, it protects the viability of chondrocytes exposed to IL‐1.…”
Section: Dexamethasonementioning
confidence: 99%
“…The microcapsules are then desiccated and stored for use. The complete details of drug loading and microsphere characteristics for antisense oligonucleotide to NF-κB, dexamethasone and the antioxidant enzyme catalase are found in recent publications (Siwale et al, 2008; Gayakawad et al, 2009; Uddin et al, 2011). …”
Section: Production Of Albumin Microspheresmentioning
confidence: 99%
“…However, the systemic administration of glucocorticoids is associated with well-known systemic side effects. Microencapsulated dexamethasone has been shown to inhibit TNF by 84%, IL1 by 93%, IL6 by 83% and IL8 by 81% after stimulation with endotoxin in a whole blood endotoxin mode (Uddin et al, 2011). This inhibition was significantly more effective in cytokine inhibition than the equivalent dose of dexamethasone given in solution.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…A robust formulation to deliver this next-generation VLP vaccine is urgently needed to make a highly efficient, cost-effective vaccine. Previously it has been found that nano-micro particle based formulation for small molecule drugs such as dexamethasone, antisense was very successful [10,11]. The similar biodegradable polymer based nanomicro particle can address the major production challenges to develop a sustainable platform in a less complicated manner, generating higher yields on a larger scale, reducing production time, and increasing costeffectiveness VLP formulation which will be next generation vaccine.…”
mentioning
confidence: 99%